(untitled) (Iranian Journal of Kidney Diseases, 2018)
Mycobacterium haemophilum is a fastidious nontuberculosis Mycobacterium that must be considered in the differential diagnosis of infections in immunocompromised patients. Mycobacterium haemophilum typically is a pathogen of the cutaneous or subcutaneous tissue and also presents as septic arthritis, osteomyelitis, pulmonary disease, and lymphadenitis. We report a 32-year-old man with past medical history of kidney transplantation, endocarditis, gastrointestinal bleeding, and hypertension, complaining of multiple painful nodular lesions since 3 months earlier. A tissue biopsy and polymerase chain reaction detected Mycobacterium haemophilum. Atypical mycobacterial species like Mycobacterium haemophilum should be assessed in immunocompromised patients positive for acid fast staining and negative for Mycobacterium tuberculosis.